Quantification of mitochondrial DNA damage and copy number in circulating blood of patients with systemic sclerosis by a qPCR-based assay - Movassaghi, Shafieh; Jafari, Sara; Falahati, Kowsar; Ataei, Mitra; Sanati, Mohammad Hossein; Jadali, Zohreh (Anais brasileiros de dermatología, 2020)
Although not fully understood, oxidative stress has been implicated in the pathogenesis of different autoimmune diseases such as systemic sclerosis. Accumulating evidence indicates that oxidative stress can induce mitochondrial DNA (mtDNA) damage and variations in mtDNA copy number (mtDNAcn). The aim of this study was to explore mtDNAcn and oxidative DNA damage byproducts in peripheral blood of patients with systemic sclerosis and healthy controls. Forty six patients with systemic sclerosis and forty nine healthy subjects were studied. Quantitative real-time PCR used to measure the relative mtDNAcn and the oxidative damage (oxidized purines) of each sample. The mean mtDNAcn was lower in patients with systemic sclerosis than in healthy controls whereas the degree of mtDNA damage was significantly higher in cases as compared to controls. Moreover, there was a negative correlation between mtDNAcn and oxidative DNA damage. The lack of simultaneous analysis and quantification of DNA oxidative damage markers in serum or urine of patients with systemic sclerosis and healthy controls. These data suggest that alteration in mtDNAcn and increased oxidative DNA damage may be involved in the pathogenesis of systemic sclerosis.